To be liked versus respected divergent goals in interracial interactions. [article]. - Bergsieker, Hilary B.
Pervasive representations of Blacks and Latinos as unintelligent and of Whites as racist mat give rise to divergent impression management goals in interracial interactions. We present studies showing that in interracial interactions racial minorities seek to be respected and seen as competent more than Whites do, whereas Whites seek to be liked and seen as moral more than racial minorities do,. These divergent impression management goals are reflected in Whites' and racial minorities' self-report responses (Studies 1a, 1b, 2, and 4) and behaviors (Studies 3a and 3b). Divergent goals are observed in pre-existing relationships (Study 2), as well as live interactions (Studies 3a, 3b. and 4). and are associated with higher level of negative other-directed affect (Study 4). Implications of these goals for interracial communication and misunderstanding are discussed.
Keywords: Interracial interactions; Intergroup contact; Impression management; Self-presentation.; non-verbal behavior